2000
DOI: 10.1002/1521-3773(20001201)39:23<4284::aid-anie4284>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Regiospecificity of Cleavage in FeIII Catecholate Complexes: Tridentate Facial versus Meridional Ligands

Abstract: A facial tridentate ligand is a key feature of iron catecholate complexes that elicit extradiol cleavage of catechols (see picture). The facial geometry allows O2 and the catecholate dianion to form a tridentate intermediate on the opposite face. Accordingly, complexes of a meridional tridentate ligand do not elicit any extradiol cleavage but instead yield quinone or result in intradiol cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 21 publications
5
110
0
Order By: Relevance
“…Also upon introducing methyl groups at amine N-atom of TACN ligand to obtain Me 3 TACN, a quantitative amount of extradiol product has been observed with any base. 41 This illustrates that the increase in Lewis acidity of the iron(III) center enhances the O 2 attack and that the steric bulk of the NMe 2 group does not discourage it. The second order reaction rate constants (table 5) of complexes [Fe(L)(DBC)(Sol)] + in DCM solvent is 19 > 18 > 17; 14 > 16 ∼ 12 > 13, which is in accordance with the decrease in Lewis acidity of the adducts in the non-coordinating solvent (cf.…”
Section: Iron(iii) Complexes Of Terminal N-alkyl// Substituted 3n Ligmentioning
confidence: 95%
See 4 more Smart Citations
“…Also upon introducing methyl groups at amine N-atom of TACN ligand to obtain Me 3 TACN, a quantitative amount of extradiol product has been observed with any base. 41 This illustrates that the increase in Lewis acidity of the iron(III) center enhances the O 2 attack and that the steric bulk of the NMe 2 group does not discourage it. The second order reaction rate constants (table 5) of complexes [Fe(L)(DBC)(Sol)] + in DCM solvent is 19 > 18 > 17; 14 > 16 ∼ 12 > 13, which is in accordance with the decrease in Lewis acidity of the adducts in the non-coordinating solvent (cf.…”
Section: Iron(iii) Complexes Of Terminal N-alkyl// Substituted 3n Ligmentioning
confidence: 95%
“…Solomon et al have very recently found that the resting extradiol-cleaving enzymes fail to react with O 2 but become reactive upon substrate binding. 35 Recent growing interest has been shifted towards the extradiol-cleaving catechol dioxygenase and their model complexes and several small molecule analogues [36][37][38][39][40][41][42][43][44] have been isolated and studied to get insight into the reaction mechanism of catechol cleavage. Earlier Funabiki et al 37 reported the first model by using FeCl 2 /FeCl 3 with pyridine/bipyridine mixture.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations